2022
DOI: 10.3390/healthcare10101917
|View full text |Cite
|
Sign up to set email alerts
|

Local Diagnostic Reference Levels for Full-Field Digital Mammography and Digital Breast Tomosynthesis in a Tertiary Hospital in Malaysia

Abstract: A set of national diagnostic reference levels (DRLs) was established in Malaysia for a range of breast thicknesses in 2013, but no updates for full-field digital mammography (FFDM) and digital breast tomosynthesis (DBT). Due to the increasing number of DBTs used and concern over radiation exposure, this study aimed to explore and establish local diagnostic reference levels for FFDM and DBT in Malaysia health facilities at different compressed breast thickness (CBT) ranges. The CBT, kilovoltage peak (kVp), Entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…The national DRL in the current study was comparable with those in Malaysia [19]. However, most countries set their DRLs for a single narrow CBT range as in Malta which was set at a CBT range of 50-70mm, while Sudan [30], and Ireland [31] set their DRLs at 55-65mm CBT range The comparison of DRLs with those of other countries is therefore challenging due to the lack of a standard CBT range used for setting the DRLs.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The national DRL in the current study was comparable with those in Malaysia [19]. However, most countries set their DRLs for a single narrow CBT range as in Malta which was set at a CBT range of 50-70mm, while Sudan [30], and Ireland [31] set their DRLs at 55-65mm CBT range The comparison of DRLs with those of other countries is therefore challenging due to the lack of a standard CBT range used for setting the DRLs.…”
Section: Discussionsupporting
confidence: 70%
“…AGD relationship with the exposure factors (kVp, mAs), ESD, CBT and Breast Compression Force (BCF) was tested using a Pearson correlation coefficient test and presented in the table form. The values of the CBT were grouped into three categories of a narrow range which were representative of CBT for the Ugandan women population as recommended by ICRP number 135 for every country to determine their women’s CBT ranges [11, 19].…”
Section: Methodsmentioning
confidence: 99%
“…The study found that the DRLs for mammography varied widely among countries, ranging from 1.5 to 3.5 mGy [ 17 , 27 ]. For example, in Malaysia, the local DRLs for full-field digital mammography (FFDM) and digital breast tomosynthesis (DBT) were established at different CBT ranges, with DBT having significantly higher AGD than FFDM [ 11 ]. In Thailand, the local DRLs for FFDM and DBT were found to be 1.65 mGy and 1.89 mGy, respectively, and were lower than the standard reference levels reported by the IAEA [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This makes it difficult to establish local DRLs for mammography in Dubai, which is crucial to ensure that patients receive a safe dose of radiation during mammography procedures. Although there are some studies on establishing local DRLs for mammography in other countries around the United Arab Emirates, such as Australia, Malaysia, and Nigeria [ 9 , 10 , 11 , 12 ], these studies may not be applicable due to differences in patient populations, equipment, and protocols. Therefore, there is a need for a study to determine local DRLs for mammography in Dubai to ensure that patients receive the appropriate dose of radiation during mammography procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation